2007
DOI: 10.1002/bit.21762
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of the energy dissipation rate in a fluorescence‐activated cell sorter: Implications to cells

Abstract: Fluorescence activated cell sorting, FACS, is a widely used method to sort subpopulations of cells to high purities. To achieve relatively high sorting speeds, FACS instruments operate by forcing suspended cells to flow in a single file line through a laser(s) beam(s). Subsequently, this flow stream breaks up into individual drops which can be charged and deflected into multiple collection streams. Previous work by Ma et al. (2002) and Mollet et al. (2007; Biotechnol Bioeng 98:772-788) indicates that subjectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 32 publications
3
72
2
Order By: Relevance
“…Mollet et al (2008) experimentally, and through CFD simulations, demonstrated that the EDR in the nozzle of FACS is sufficient to damage a number of different cell lines, including CHO cells. Table 2 and Fig.…”
Section: Cell Damage In Downstream Equipment and Other Bioprocess Equmentioning
confidence: 99%
“…Mollet et al (2008) experimentally, and through CFD simulations, demonstrated that the EDR in the nozzle of FACS is sufficient to damage a number of different cell lines, including CHO cells. Table 2 and Fig.…”
Section: Cell Damage In Downstream Equipment and Other Bioprocess Equmentioning
confidence: 99%
“…Figure 3 presents the result of these acute exposure studies to five different flow rates (10, 30, 50, 70, and 90 mL min respectively, Mollet et al, 2007). In addition, data from previously published studies using CHO K1 cells, MCF-7, and THP-1 cells are included for comparison (Ma et al, 2002;Mollet et al, 2007Mollet et al, , 2008. As can be observed by inspection of Figure 3, the response of the current CHO cell line is consistent with the response of previously used CHO K1 with respect to the level of EDR at which significant cell lysis occurs.…”
Section: Acute Exposure To High Edrmentioning
confidence: 99%
“…Response of CHO cells used in this study to an acute exposure to the hydrodynamic forces created by the TC and characterized by a specific level of EDR. As reference points, data from previously published studies with CHO K1 cells, MCF-7, and THP1 cells are presented (Ma et al, 2002;Mollet et al, 2007Mollet et al, , 2008. Dashed lines indicate the flow rate for every EDR.…”
Section: à3mentioning
confidence: 99%
“…19,31,33 Lokhandwalla and Sturtevant, 31 for example, noted the presence of extensional flow with hemolysis from shock wave lithotripsy. When working with hamster ovary cells, Mollet et al 34 found that high levels of cell damage were seen in areas of high extensional stress. Although ovarian cells are much different from red blood cells, it would not be unreasonable to assume the same mechanisms might affect RBCs and ovarian cells alike.…”
Section: Introductionmentioning
confidence: 99%